A new species of sinistral flatfish of the genus Chascanopsetta (Teleostei: Bothidae) from off Papua New Guinea, western Pacific Ocean - Tongboonkua, Pakorn; Lee, Mao-Ying; Chen, Wei-Jen (Zootaxa, 2018)
Left-eyed flounders of the genus Chascanopsetta Alcock 1894 (Bothidae) occur in the Indian, Pacific, and Atlantic oceans at depths ranging from 120 to 1500 meters. They possess some unique features in bothid fishes including a strongly compressed and elongated body and a tremendously large mouth. Currently, nine species of Chascanopsetta are recognized, and three of them (C. micrognatha Amaoka & Yamamoto 1984, C. lugubris Alcock 1894 and C. prognatha Norman 1939) are distributed in the West Pacific. We collected 25 specimens of Chascanopsetta during 11 biodiversity expeditions carried out mainly in the West Pacific. Among them, eight specimens taken off Papua New Guinea present morphological features that differ from those of the three nominal species known in the West Pacific. In this study, we examined these eight specimens of unknown affinity and compared their morphology to that of specimens of other congeneric species. Results of these comparisons showed that these specimens represent an undescribed species of Chascanopsetta, named herein, C. novaeguineae sp. nov.. The new species resembles C. elski Foroshchuk 1991, which is known only from the Saya de Malha Bank in the western Indian Ocean, in having a high number of gill rakers (> 13). However, the combination of the following characters further distinguishes C. novaeguineae sp. nov. from C. elski: longer jaws, narrower interorbital width, and number of pseudobranches (21–25 vs. 26–27). The DNA sequences from the mitochondrial cytochrome oxidase subunit I (COI) gene from C. novaeguineae sp. nov. and other species were obtained and compared to confirm its taxonomic status and to infer its tentative phylogenetic position within the Chascanopsetta.